MELATIH PSIKOMOTORIK GENERASI SEDARI DINI SIAGA BENCANA (GEGANA) MURID TK PEMBANGUNAN UNIVERSITAS NEGERI PADANG - Dharmawan, Andre; Audyshia Rifa Charisma Sakti; Nurmi Putri Rahayu; Muhammad Fadlan Sadli; Audrey Shaquilla (Universitas Negeri Padang, 2023)
The earthquake that occurred in the last few years in Indonesia certainly damaged infrastructure in general, such as schools, houses of worship, health facilities, residential areas, and others in Indonesia. Children are a vulnerable group and have high sensitivity during disasters, so special attention is needed. Children can be involved as potential agents of disaster management by being given knowledge of first aid in accidents. Therefore, children must be accustomed to applying what they have learned. The psychomotor domain is a method that combines the use of the functions of the nervous, muscular and psychic systems which are considered appropriate as learning methods for children. This psychoeducation involved 18 children from the Padang State University Development Kindergarten through coloring and singing methods accompanied by movement. After psychoeducation is given, children are proficient in imitating movements that can save them from earthquakes